Effects of olanexidine gluconate on preoperative skin preparation: an experimental study in cynomolgus monkeys. Issue 5 (May 2017) - Nakata, Hikaru; Tsubotani, Yoshie; Nii, Takuya; Hagi, Akifumi; Inoue, Yasuhide; Imamura, Tadashi
Abstract : Purpose. : To determine the bactericidal efficacy of a new topical antiseptic for preoperative skin preparation, olanexidine gluconate (development code: OPB‐2045G), against transient or resident bacterial flora on the skin of cynomolgus monkeys. Methodology. : After measuring baseline bacterial counts on test sites marked on the abdomens, we applied olanexidine, chlorhexidine or povidone‐iodine. After 10 min (fast‐acting effect) and 6 h (long‐lasting effect), bacterial counts were measured again and log10 reductions were calculated. In addition, we determined the bactericidal effects on the skin contaminated with blood before or after applying the antiseptics. Results. : In the non‐blood‐contaminated condition, the mean log10 reductions of olanexidine at doses of 1‐2% were significantly higher than those of saline (negative control), but did not significantly differ from those of 0.5% chlorhexidine and 10% povidone‐iodine at either time point. But olanexidine was significantly more effective at both time points than chlorhexidine and povidone‐iodine when applied after the site was contaminated with blood. Olanexidine was also significantly more effective than chlorhexidine and as effective as or more effective than povidone‐iodine at both time points when skin was contaminated with blood after the antiseptics were applied. Conclusion. : The bactericidal effects of olanexidine were comparable to those of commercial antiseptics such as chlorhexidine and povidone‐iodine in non‐blood‐contaminated conditions. More importantly, the effect of olanexidine was hardly affected by blood unlike commercial antiseptics. Thus, it is considered that olanexidine has a favourable property for skin preparation in various types of surgical treatments.